Climate mediates phenological and phylogenetic differentiation in plant invasions - Tadeo H. Ramirez-Parada; Isaac W. Park; Shijia Peng; Misako Nishino; John T. Kartesz; Sydne Record; Charles C. Davis; Susan J. Mazer (Proceedings of the National Academy of Sciences, 2026)
Darwin’s Naturalization Conundrum holds that both functional similarity and distinctiveness can facilitate biological invasions: invaders similar to natives may succeed through preadaptation to local abiotic conditions, whereas functionally distinct invaders may succeed by reducing competition. Yet the contexts in which either mechanism dominates are unclear. Prior research has primarily attributed variability in native–invasive differentiation to shifts in the balance between biotic and climatic barriers to invasion from local to regional scales. However, similarity and distinctiveness are frequent at both local and regional levels, indicating key drivers of native–invasive differentiation remain overlooked. Crucially, theory and evidence show that as climatic stress increases, competition weakens. This implies that harsh climates should favor invaders functionally similar to natives, whereas mesic climates should favor distinctiveness. However, this hypothesis has not been tested across climate regimes and functional traits. We addressed this gap by combining models of species distributions and flowering phenology for 2,810 species across the United States, estimating phylogenetic distance and phenological differentiation between natives and invasives relative to differentiation among co-occurring natives. In warm, humid regions, invasives flowered earlier, less synchronously, and were more distantly related to natives. In cold or dry regions, they flowered at similar or later times, more synchronously, and were more closely related than natives themselves. Across all climates, invasives consistently exhibited longer flowering durations, with little evidence of greater phenological plasticity. These findings reveal that Darwin’s Conundrum reflects a predictable continuum shaped by environmental context, highlighting climate as a key axis of invasion success.